The effect of online learning on students’ understanding of football learning during the Covid-19 pandemic - Komarudin Komarudin; Rizka Prihandana Nugraha (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
This study aims to determine the effect of online learning on students' understanding of football material during the COVID-19 pandemic. The type of research used is quantitative research with an associative approach, research that seeks a causal relationship between one variable X and variable Y. The data collection technique used in this study is a survey method with instruments in the form of questionnaires and multiple-choice tests. The subjects in this study were students of Aisyiyah Fullday Wedi Junior High School class VIII, Klaten Regency, Central Java Province amounting to 87 people who were determined using the Total Sampling technique. The data analysis technique used in this study is to use statistics with the F test and Product Moment. The results of the study indicate that there is an effect of online learning on students' understanding of football material at Junior High School Aisyiyah Fullday Wedi, Klaten Regency, Central Java Province during the Covid-19 pandemic. This can be seen from the simple linear regression equation Y= 9.610 + 0.413 X and the close relationship between X variable (online learning) and Y variable (understanding football material) which is 0.694 so it is included in the level of a strong relationship. And the contribution (donations) that exist in the X variable to the Y variable is 4.82% while 95.18% is influenced by other variables. From these results, it can be seen that there is an increase or decrease in students' understanding of football material, one of which is influenced by Online Learning at Aisyiyah Fullday Wedi Junior High School, Klaten Regency, Central Java Province.Pengaruh pembelajaran daring terhadap pemahaman materi sepakbola peserta didik pada masa pandemi Covid-19AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh pembelajaran daring terhadap pemahaman materi sepakbola pada peserta didik pada masa pandemi coovid-19. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan pendekatan asosiatif, penelitian yang mencari hubungan sebab akibat antara satu variabel X dengan variabel Y. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu metode survei dengan instrumen yang berupa angket dan tes soal pilihan ganda. Subjek dalam penelitian ini adalah peserta didik Sekolah Menengah Pertama Aisyiyah Fullday Wedi, Kabupaten Klaten, Provinsi Jawa Tengah kelas VIII yang berjumlah 87 orang yang ditetapkan menggunakan teknik Total Sampling. Teknik analisis data yang digunakan dalam penelitian ini adalah dengan menggunakan statistik dengan uji F dan Product Moment. Dari hasil penelitian menunjukkan bahwa terdapat pengaruh pembelajaran daring terhadap pemahaman materi sepakbola peserta didik di Sekolah Menengah Pertama Aisyiyah Fullday Wedi, Kabupaten Klaten, Provinsi Jawa Tengah pada masa pandemi Covid-19. Hal ini dapat dilihat dari persamaan regresi linier sederhana Y = 9,610 + 0,413X dan keeratan hubungan variabel X (pembelajaran daring) terhadap variabel Y (pemahaman materi sepakbola) yaitu sebesar 0,694 sehingga termasuk dalam tingkat hubungan yang kuat. Serta Kontribusi (sumbangan) yang ada pada variabel X terhadap variabel Y sebesar 4,82% sedangkan 95,18% dipengaruhi oleh variabel lain. Dari hasil tersebut terlihat meningkat atau menurunnya pemahaman peserta didik pada materi sepakbola salah satunya dipengaruhi oleh Pembelajaran Daring di Sekolah Menengah Pertama Aisyiyah Fullday Wedi, Kabupaten Klaten, Provinsi Jawa Tengah.